Pengaruh Testimoni Terhadap Keputusan Pembelian Melalui Aplikasi Shopee di Kabupaten Tebo - Haikal Pratama; Uli Haflita (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research aims to determine the influence of testimonials on purchasing decisions via the Shopee Application in Tebo Regency. The type of research used is quantitative descriptive through the results of distributed questionnaires. The population used in this research is all consumers who have purchased products via the Shopee Application in Tebo Regency, the exact number of which is unknown. The sampling technique was carried out using a purposive sampling method of 70 people. Results of data analysis using simple linear regression. The research results show that there is a significant influence of testimonials on purchasing decisions via the Shopee Application in Tebo Regency.